Internationalisation of the world retail congress: A Strategic market Analysis - Hansotia, Shahen (2011)
This management project is carried out keeping in mind the client organisation, EMAP ltd’s retail event ‘The World Retail Congress’ who I am currently interning with. It is an annual event which is hosted at different venues each year mainly in Western Europe. As the name might suggest, it is a world event catering to various genres of retail like fashion, FMCG, DIY, grocery, technology etc and is a one stop shop for retailers, vendors and support partners (IT services, banks etc) and suppliers around the world to learn, benchmark and discuss best practices all under one roof over the period of four days. However, a very high majority of the attendees of the event each year come from Western Europe and North America. It may be that the content had been tailored to cater to the big players hailing from these two continents or the fact that small and medium retailers prefer to attend similar events or exhibitions locally at a smaller scale. However, due to the economic crisis that the world faces today, retail is one among many industries/sectors which has seen a steep decline in numbers and growth especially in saturated markets of North America and Western Europe. On the other hand, analysts suggest that emerging markets in regions like Asia, Middle East, Latin America, Eastern Europe etc have shown unprecedented growth in their national GDP’s and the prospects of future growth in retail seem very attractive to foreign investors and domestic players alike. The bullish nature of these regions and the upward pointing graph of retail have been identified by EMAP ltd and they wish to provide a similar platform to retailers within those specific regions and replicate the success of the world retail congress in those regions with a local flavour to it. To do this, the EMAP ltd would be looked at from the ‘resource based view’ perspective for formulating a robust strategy to internationalise the world retail congress. For the sake of this report, three major regions would be reviewed namely Middle East, Eastern Europe and Latin America. Each region would be looked at in isolation in terms of the national GDP, overall retail industry, identifying the major retailers and revenues (international and domestic players), forecasted growth, sophistication of the region in terms of logistics and technology etc. Political risk is also a factor which would be looked at for the company to make an informed investment decision. The competitive landscape within each region would also be looked at in terms of other conferences/business events in a particular region or country, number of attendees, b2b publications and an estimate of costs involved. A crucial factor amongst all would be the suitability of a particular city or country within a region for hosting the said event in terms of transport and location infrastructure. A qualitative analysis would be undertaken to find out first hand from the retailers about what their preferences are and what is missing in their geography. Although doing everything mentioned above for all three regions may be a bit ambitious, it has been agreed by the company that the objective of the report would be to go for breadth and not for depth to simply get an overview of what might be in store for them and may consider looking into it further into a region depending upon the findings and recommendations made at the end.